Extracting Named-Entities and their Relationships - Oliveira, Elias; Dias, Gabriel; Lima, Jaimel; Pirovani, Juliana (Journal of Information and Data Management, 2023)
Extracting named entities from an unstructured text is a good form to build knowledge for conversational intelligent systems. Named Entity Recognition aims to automatically identify and classify entities like persons, places, organizations, and so forth. In addition, Named Entity Recognition is also a fundamental step for relations extraction. However, both problems are hard to solve, as several categories of named entities are similarly written and appear in cognate contexts. To accomplish it, some hybrid approaches combining machine learning and expert linguistic tailored models are usually used. In this current study, we turn our focus onto the expert linguistic flavor by applying Local Grammar and Cascade of Transducers. Local Grammars are to represent the rules of a particular linguistic structure. They are often built manually to describe the entities and relations we aim to recognize. In our study, we adapted a Local Grammar to improve the Recognition of Named Entities. The results show an improvement of up to 7% on the F-measure metric in relation to the previous Local Grammar. Besides, we built another Local Grammar to recognize binary relationships between person and person linked by parenthood and person and localization linked by a recognized place of birth from the improved Local Grammar. Finally, we present practical applications for a conversational system using Prolog for inferring over the extracted entities and relations.